Immunohistological expression of oestrogen receptor, progesterone receptor, mammaglobin, human epidermal growth factor receptor 2 and GATA-binding protein 3 in non-small-cell lung cancer - Kriegsmann, Katharina; Zgorzelski, Christiane; Muley, Thomas; Christopoulos, Petros; Winterfeld, Moritz von; Herpel, Esther; Goeppert, Benjamin; Mechtersheimer, Gunhild; Sinn, Peter; Stenzinger, Albrecht; Schirmacher, Peter; Winter, Hauke; et al. (Histopathology, 2020)
Aims Non-small-cell lung cancer (NSCLC) and breast cancer are common entities. Staining for oestrogen receptor (ER), progesterone receptor (PgR), mammaglobin (MAMG) and GATA-binding protein 3 (GATA3) is frequently performed to confirm a mammary origin in the appropriate diagnostic setting. However, comprehensive data on the immunohistological expression of these markers in NSCLC are limited. Therefore, the aim of this study was to analyse a large cohort of NSCLCs and correlate the staining results with clinicopathological variables. Methods and results A tissue microarray was stained for ER, PgR, MAMG, human epidermal growth factor receptor 2 (HER2), and GATA3, and included 636 adenocarcinomas (ADCs), 536 squamous cell carcinomas (SqCCs), 65 large-cell-carcinomas, 34 pleomorphic carcinomas, and 20 large-cell neuroendocrine carcinomas. HER2 status was determined for immunohistochemically positive cases with chromogenic in-situ hybridisation. Markers with a proportion of ≥5% positive cases in ADC and SqCC were considered for survival analysis. Among ADCs, 62 (10%), 17 (3%), one (<1%), seven (1%), and 49 (8%) cases were positive for ER, PgR, MAMG, HER2, and GATA3, respectively. Among SqCCs, 10 (2%), 14 (3%), two (<1%) and 109 (20%) cases were positive for ER, PgR, HER2, and GATA3, but none of the samples showed positivity for MAMG. ER positivity was associated with ADC, female sex, smaller tumour size, and lower clinical stage. None of the markers had an impact on survival. Conclusion We report on ER, PgR, MAMG, HER2 and GATA3 expression in a large cohort of NSCLCs. Interpretation of these markers in the differential diagnostic setting should be based on a multimarker panel.
Published online Article accepted 7 July 2020
Gesehen am 06.12.2021